The Final Power of the Decision of the Constitutional Court in Indonesian Positive Law - Indra Lesmana; Ardiansah Ardiansah; Bahrun Azmi (Budapest International Research and Critics University, 2022)
The decision of the Constitutional Court is final and binding, therefore it must be obeyed by anyone without exception. In the constitutional law order, especially with regard to the decisions of the Constitutional Court, it is known that the Erga Omnes principle is applied, which means that the decisions of the Constitutional Court must be obeyed by anyone, not only by litigants. The main research problem is what is the final character of the decision of the Constitutional Court according to Indonesian positive law and what is the most ideal reconceptualization of the final strength of the Constitutional Court Decision. This type of research is normative legal research. The data source comes from secondary data which is divided into 3 types of data, namely primary, secondary and tertiary legal materials. The conclusions of this study are, First, the final power of the Constitutional Court Decision in Indonesian Positive Law is expressly regulated in Article 24C Paragraph (1) of the 1945 Constitution, Article 10 of Law Number 24 of 2003 concerning the Constitutional Court Article 29 Paragraph (1) Law Number 48 of 2009 concerning Judicial Power. Second, the most ideal reconceptualization of the final strength of the Constitutional Court Decisions needs to be carried out to maintain the purity of the Constitutional Court as the Guardian of the Constitution, by: Affirming the Erga Omnes Principle in the Constitutional Court Law, Responsiveness of Executive and Legislative Institutions and Its Relation to Responsive Legal Theory , Reasons for Delaying Final Strength of Constitutional Court Decisions, Constitutional Court Decisions as Ius Constituendum in Legal Politics Perspective, Accelerating Progress on Draft Laws on Contempt of Court, Ideas for Incorporating Constitutional Court Decisions into the Hierarchy of Legislation.